SYNCRETIC RITUALS IN SUNDANESE AGRICULTURE: A PHILOLOGICAL STUDY OF THE MELAK PARE MANUSCRIPT - Solehudin, Solehudin; Supriadi, Dedi (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2025)
This research examines the physical characteristics and textual content of the Melak Pare manuscript, a significant cultural artifact within Sundanese heritage. The research aims to enhance public understanding of this manuscript by providing a detailed description and analysis. Employing historical methodology, including heuristics, verification, interpretation, and historiography, this research draws on primary data from the original Melak Pare manuscript housed at the Sri Baduga Museum in Bandung, as well as secondary sources such as books, scholarly articles, and related documents. The findings show that the manuscript is written on yellowed European-style paper that has been reinforced with Japanese tissue as a preservation measure. The script used is Arabic Pegon, resembling standard Arabic script yet exhibiting distinct compositional features unique to local usage. The content consists of agricultural mantras integral to traditional Sundanese agrarian practices. These mantras incorporate ritual actions and invoke Nyimas Puhaci Sanghyang Sri, widely known as Dewi Sri, alongside prayers modeled on Islamic traditions. The manuscript thus reflects a process of cultural assimilation, illustrating the emergence of a hybrid cultural form shaped by prolonged interaction between indigenous Sundanese and Islamic influences. Keywords: Manuscripts, Mantras, Melak Pare, Dewi Sri, Pegon